Estimation of Ionospheric Conductivity Based on the Measurements by Superdarn - Eun Ah Lee; Byung-Ho Ahn; Yu Yi (Journal of Astronomy and Space Sciences, 2002)
The ionosphere plays an important role in the electrodynamics of space environment. In particular, the information on the ionospheric conductivity distribution is indispensable in understanding the electrodynamics of the magnetosphere and ionosphere coupling study. To meet such a requirement, several attempts have been made to estimate the conductivity distribution over the polar ionosphere. As one of such attempts we compare the ionospheric plasma convection patterns obtained from the Super Dual Auroral Radar Network (SuperDARN), from which the electric field distribution is estimated, and the simultaneously measured ground magnetic disturbance. Specifically, the electric field measured from the Goose Bay and Stokkseyri radars and magnetic disturbance data obtained from the west coast chain of Greenland are compared. In order to estimate ionospheric conductivity distribution with these information, the overhead infinite sheet current approximation is employed. As expected, the Hall conductance, height-integrated conductivity, shows a wide enhancement along the center of the auroral electrojet. However, Pedersen conductance shows negative values over a wide portion of the auroral oval region, a physically unacceptable situation. To alleviate this problem, the effect of the field-aligned current is taken into account. As a result, the region with negative Pedersen conductance disappears significantly, suggesting that the effect of the field-aligned current should be taken into account, when one wants to estimate ionospheric conductance based on ground magnetic disturbance and electric field measurements by radars.